Pengaruh High Intensity Interval Training Terhadap Cardiorespiratory Pada Remaja - Yoga Handita Windiastoni; Nurul Fithriati Haritsah (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Cardiorespiratory fitness in adolescence affects the level of fitness and determinants of health levels in old age. School adolescents who have low physical activity need easy, efficient and effective physical training to increase cardiorespiratry fitness, namely high intensity interval training. Objective: to determine the effect of high intensity interval training on cardiorespitatory fitness training in adolescents. Subjects: 60 high school students (men n = 21, women n = 39) aged 15-19 years who met the study criteria and were divided into 2 groups, a high intensity interval training group and a control group by jogging. Method: quasi experimental with pre-test and post-test one group design with control group. The instrument used in this study was a 20m shuttle run test. Analysis: normality test with Kolmogorov-Smirnov, then parametric test with paired sample t-test and parametric difference test with independent sample t-test. Results: VO2max pre-test and post-test high intensity interval training group obtained p value = 0,000 (p <0.05) which showed there were significant differences before and after treatment. The results of the post-test different test between the control and treatment groups showed that the value of p = 0,000 (p <0.05) showed that there was a significant difference between the high intensity interval training group and the control group and the results of the different mean mean were greater in the high intensity interval training group. after and before treatment. Conclusion: high intensity interval training can increase cardiorespiratory fitness in adolescents according to the results of VO2max values.